1993
DOI: 10.1007/bf01321781
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia in systemic disease

Abstract: Dysphagia, difficulty in swallowing sometimes accompanied by a sensation of food sticking, is a common symptom resulting from structural and/or motility disorders of the oropharynx and esophagus which may result from local factors or occur as one of the manifestations of a systemic disease process. In this review, "systemic disease" will include diseases that affect more than one organ or organ system in the body such as scleroderma or Crohn's disease; skin disorders such as epidermolysis bullosa dystrophica a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 100 publications
(60 reference statements)
0
9
0
Order By: Relevance
“…In a number of cases swallowing disorders reflect a convergence of mixed, unrelated, or undiagnosed conditions 10 …”
Section: Dysphagia From Systemic Composite or Unknown Mechanismsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a number of cases swallowing disorders reflect a convergence of mixed, unrelated, or undiagnosed conditions 10 …”
Section: Dysphagia From Systemic Composite or Unknown Mechanismsmentioning
confidence: 99%
“…In a number of cases swallowing disorders reflect a convergence of mixed, unrelated, or undiagnosed conditions. 10 The inflammatory diseases potentially affecting swallowing are too numerous to be fully reviewed here. 10 In addition to various forms of pharyngitis produced by a number of common bacteria and viruses, varieties of neurotoxins, such as those produced in diphtheria, rabies, and tetanus, may lead to soft palate and pharyngeal paralysis.…”
Section: Dysphagia From Systemic Composite or Unknown Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Manometric evaluation of the pharynx, P-E segment, and cervical esophagus revealed reduced generation of swallowing pressure.45 Radiographic studies have demonstrated pharyngeal weakness with barium retention in both the valleculae and piriform sinuses that may result in airway penetration, tracheal aspiration, or nasoregurgitation. 46 Sonies and co-workers47 studied three patients with DM, using ultrasound and the modified barium swallow. Their patients had both oral-and pharyngeal-stage disorders.…”
Section: Dermatomyosztzsmentioning
confidence: 99%